Coronary Artery Disease and Fibrinolysis: From the Blood to the Vessel Wall - Sobel, Burton E. (Thrombosis and Haemostasis, 1999)
This review addresses a continuum of the role of derangements in the fibrinolytic system from the blood to the vessel wall in the pathogenesis of acute coronary events and the underlying vasculopathy. Pharmacologic modification of fibrinolysis has become a primary therapy for acute myocardial infarction caused by thrombotic occlusion of infarct-related coronary arteries. Patients with type 2 diabetes and other insulin resistant states exhibit impaired fibrinolysis in blood, implicated in the pathogenesis of macroangiopathy. An altered balance of activity of proteins involved in the fibrinolytic system within vessel walls (the proteo[fibrino]lytic system) has been recognized as well and appears likely to contribute to the acceleration of macroangiopathy. Accordingly, normalization of the proteo(fibrino)lytic system in blood and in vessel walls is a particularly attractive target for retardation of the progression of macrovascular disease associated with insulin resistant states.
Keywords: PAI-1; tPA; clot lysis; thrombosis; atherosclerosis; plaque vulnerability